2017
DOI: 10.1038/s41598-017-15925-1
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Reduces Blood Pressure and Attenuates Oxidative Stress and Cardiac Hypertrophy in Spontaneously Hypertensive Rats

Abstract: Gallic acid (GA) has been reported to have beneficial effects on cancer, vascular calcification, and diabetes-induced myocardial dysfunction. We hypothesized that GA controls hypertension via oxidative stress response regulation in an animal model for essential hypertension. Spontaneously hypertensive rats (SHRs) were administered GA for 16 weeks. GA treatment lowered elevated systolic blood pressure in SHRs through the inhibition of vascular contractility and components of the renin-angiotensin II system. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 60 publications
2
57
0
1
Order By: Relevance
“…It has been demonstrated that oxidative stress plays an important role in cardiac hypertrophy and remodeling (Jin et al, ; Seddon, Looi, & Shah, ). To elucidate the potential role of FoxO3 in PQ‐induced cardiac damage, we generated cardiomyocyte‐specific FoxO3 knockout (CKO) mice by crossing FoxO3 f/f with Myh6‐Cre mice (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that oxidative stress plays an important role in cardiac hypertrophy and remodeling (Jin et al, ; Seddon, Looi, & Shah, ). To elucidate the potential role of FoxO3 in PQ‐induced cardiac damage, we generated cardiomyocyte‐specific FoxO3 knockout (CKO) mice by crossing FoxO3 f/f with Myh6‐Cre mice (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Protocatechuic acid is known as having suppressive effect on TNBS-induced colitis [ 15 ], preventive effect on LPS-induced inflammatory response in fibroblast [ 16 ], and anti-oxidative effect [ 17 ]. In addition, gallic acid has several effects on allergic reaction [ 18 ], type 2 diabetes symptoms [ 19 ], oxidative stress, and hypertension [ 20 ]. These constituents (protocatetuic acid and gallic acid) might influence the regulatory effect of ES on P.acnes -induced ear inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…There are many natural sources of GA, either in its free state or as part of tannin molecules in various fruits (Kuppan et al, ; Li, Liu, Zhao, Xi, & Niu, ). Furthermore, GA also has anti‐mutagenic, anti‐carcinogenic, anti‐allergic and anti‐bacterial abilities (Li et al, ) and has important roles in the cerebral antioxidant system (Naghizadeh & Mansouri, ) and in mitigating cardiac hypertrophy (Jin et al, ).…”
Section: Introductionmentioning
confidence: 99%